Strategi Pengembangan Kompetensi Digital SDM melalui Upskilling dan Reskilling - Benny Tunggul Hasiholan; Yunia Vivi Kartika; Naufal Naufal (Institut Nalanda, 2026)
his guide is a new format and template for manuscripts/articles used by lecturers/researchers/practitioners/students which will be published in PUBLIC journals starting publication in 2020. Articles begin with article title, author's name, author's affiliation, email, followed by an abstract in two Language, namely Indonesian abstract and English abstract. Specifically, English abstracts are written in italics (Italic) for 150-200 words. Abstract in justify form with a font size of 11 pt and Times New Roman font and one space between lines. If the article is in Indonesian, the abstract must be written in good and correct Indonesian and English. If the article is in English, the abstract must be written in English only. The abstract contains research objectives, research methods, data collection techniques, research results and discussion and conclusions. The abstract begins with the words